Using a Multilevel Governance Framework for the Reform of the International Investment Law Architecture - Mpofu, Kathleen (University of the Witwatersrand, Johannesburg, 2024)
International investment law has come under significant scrutiny over the last few years under what has been termed as a legitimacy crisis, with various stakeholders expressing concerns regarding its operation. These concerns cover both the substantive and procedural aspects of international investment law. In response to these concerns, states have, at varying levels of governance, taken steps to reform the international investment law system with some states focusing on procedural reforms and others focusing on substantive reforms. This thesis considers the effectiveness of the reform process taking place in the international investment law system and finds that the piecemeal and fragmented approach that has been adopted by states may not be able to address the wide range of concerns raised by stakeholders. The achievement of effective reform requires a holistic approach that not only focuses on systemic change in redesigning investment treaties but also on national reforms. This approach has largely been absent in the reform process. The question that arises is how to develop a system of international investment law, that can effectively regulate the relationships and tensions that arise in the use of FDI, that incorporates the needs of all stakeholders and allows the different levels of governance to effectively participate in the system. This thesis explores alternative methods of reform that go beyond the small mandate of the Working Group III reforms currently being discussed and that can adequately address broader concerns that arise within the international investment law system that affect the needs of other stakeholders beyond the needs of investors. In order to do this, the thesis made use of the multilevel governance framework to effectively organise and incorporate the different stakeholders and different levels of governance into the international investment law system. The principles that apply in the multilevel governance framework are useful in shifting the reform discussions from the narrow focus currently present in the reform effort, to exploring a wider range of issues and concerns faced by a wider range of stakeholders and proposing inclusive solutions that share and balance power between the different levels of governance. To rebalance the rights and protections granted in IIAs and incorporate the different levels of governance into the international investment law framework, the thesis clarifies the right to regulate by embedding it as a principle of customary international law, applicable regardless of its incorporation in the treaty. To allow for broader public interest considerations such as sustainable development to be incorporated into IIAs, the thesis proposes the use of framework v clauses (which operate much like framework agreements) in the text of the IIA which will establish the broader commitments of the parties and leave the setting of specific targets to national legislation. In so doing, regulatory power can be shared between the different levels of governance using the multilevel governance principles, allowing states to enact meaningful regulatory measures within the scope of the right to regulate. To incorporate the national level of governance in the dispute settlement process, the thesis recommends the incorporation of the exhaustion of local remedies rule and sets out how the competence to settle disputes can be shared between the national and international level in a manner that limits contestation and enhances co-operation. This is coupled with the creation of a multilateral investment court at the international level of governance that does away with the use of arbitration as a mode of dispute settlement, has a more court like structure, with increased rights of access and participation for third parties who can actively participate in the dispute settlement process and have their rights vindicated by the court. In this way, the recommendations in the thesis allow for the regulation of the different relationships that arise in the use of foreign direct investment and creates an international investment law system where the achievement of investment objectives and economic growth need not come at the expense of other equally important public international law considerations.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy, In the Faculty of Faculty of Commerce, Law and Management, School of Law, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; multilevel governance; reform; international investment law; SDG-8: Decent work and economic growth